2018
DOI: 10.1021/acsnano.8b07671
|View full text |Cite
|
Sign up to set email alerts
|

Nanocombing Effect Leads to Nanowire-Based, in-Plane, Uniaxial Thin Films

Abstract: The fabrication of thin films comprising ordered nanowire assemblies with emerging, precisely defined properties and adjustable functionalities enables highly integrated technologies in the fields of microelectronics and micro system technology, as well as for efficient power generation, storage, and utilization. Shear force, theoretically, is deemed the most promising method for obtaining in-plane, uniaxial thin films comprising nanowires. The success depends largely on the assembly process, and uniform struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…It has been previously reported that CNCs can aid in aligning high-aspect-ratio nanowires by preventing aggregation and enhancing orientational order. 34,35 In our case, CNCs facilitate the alignment of much smaller nanorods under shear. Our observation of uniaxial alignment of coassembled composite system is consistent with oriented, low-aspect-ratio gold nanorods mixed with CNCs as demonstrated by Liu et al 20 Although Liu's study was limited to low loading of gold nanorods, they did not calcine the material to remove organics.…”
Section: ■ Introductionmentioning
confidence: 63%
“…It has been previously reported that CNCs can aid in aligning high-aspect-ratio nanowires by preventing aggregation and enhancing orientational order. 34,35 In our case, CNCs facilitate the alignment of much smaller nanorods under shear. Our observation of uniaxial alignment of coassembled composite system is consistent with oriented, low-aspect-ratio gold nanorods mixed with CNCs as demonstrated by Liu et al 20 Although Liu's study was limited to low loading of gold nanorods, they did not calcine the material to remove organics.…”
Section: ■ Introductionmentioning
confidence: 63%
“…48 Although the detailed mechanism of in situ, oxidative polymerization remained in debate, 49 our previous studies have verified that individual V 2 O 5 •nH 2 O nanofibers functioned as sacrificing templates for the formation of nanofibrous PANI. 46,50 Based on the hydrophobic interparticulate interactions between nanofibrillar PANI, multiple structural forms such as thin films, 46 fibers, 51 and 3D networks 50,52 could be permanently maintained after oxidative polymerization using V 2 O 5 •nH 2 O dispersions or (thin) films as oxidant agents. It is worth noting that the method based on in situ, oxidative polymerization was equally valid for the fabrication of other conducting polymers including polypyrrole 50,53 and poly(3,4-ethylenedioxythiophene).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the interactions between V 2 O 5 · n H 2 O nanofibers are so strong that adjacent nanofibers tend to be mutually oriented in each nematic polydomain in a spontaneous manner. The ordering can be preserved or enhanced permanently in continuous V 2 O 5 · n H 2 O films and thin films , after solvent removal. In short, both extreme aspect ratios and rich interfacial hydroxy groups guarantee strong interparticulate interactions between V 2 O 5 · n H 2 O nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…Certainly, it has been challenging to arbitrarily arrange nanowire into compact and desired geometry, but the recently reported bottom-up technologies endow the ability to assemble well-aligned nanowire arrays in a predesigned way with higher precision for practical applications. [117,118] There have been very good review focused on NWs assembly in recent years; [31,119,120] hence, we only provide a brief introduction on NWs assembly and pay close attention to analyzing the effect of the macrostructures on the sensing performances of the devices. Briefly, the choice for the method of transferring NWs onto flexible substrates is mainly determined by the synthesis process of the NWs.…”
Section: Assembly Methods For Nanowire-based Sensorsmentioning
confidence: 99%